KNOWLEDGE AND ADOLESCENT SEXUAL ACTIVITY OF SENIOR HIGH SCHOOL LEVEL IN DISTRICT KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2014)
Background: Adolescence is a period of transition from children to adults, both physically and psychologically, including their social aspects. At this time, knowledge about sexuality is needed, so they can avoid unwanted pregnancy, sexually transmitted diseases, expelled from school, unsafe abortion and even death. Good knowledge will form a positive attitude and is expected to grow into healthy adults sexually. Based on Survey of Indonesian Family Planning Association ( PKBI ) in Central Java on adolescent behavior when dating mention chat with each other 100%, hold hands 93. 3 %, kiss on the cheek or forehead 84. 6 %, kissing lips 60. 9 %, kissing the neck 36. 1 %, touching and being touched ( breast and private organs ) 25 %.  Objective: To determine knowledge and adolescent sexual activity of senior high school level students in district Klaten.  Methods: The study was descriptive quantitative with time point approach. Total sample of 68 students.  Results: Knowledge of senior high school level students in district Klaten on sexuality fall category of good 56 students (82 %), enough 12 students (18 %) and less 0 %. Sexual activity include interest in the opposite sex 98 %, saw a porn movie 19 %, holding hands 84%,masturbation 0%, lip kiss 15 %, kissing the neck 3 %, petting 0 %, intercouse 0 %.  Conclusion : Knowledge of senior high school level students in district Klaten about sexuality majority fall into the category of good 56 students (82 %). Sexual activity has exceeded the limits of reasonableness student sexual development for adolescents are just beginning to fantasize about things related to sex.